Maternal Nicotine Exposure Alters Hippocampal Microglia Polarization and Promotes Anti-inflammatory Signaling in Juvenile Offspring in Mice - Zhou, Li; Tao, Xinrong; Pang, Gang; Mu, Min; Sun, Qixian; Liu, Fei; Hu, Yuting; Tao, Huihui; Li, Bing; Xu, Keyi (Frontiers in Pharmacology, 2021)
Accumulating evidence reveal that maternal smoking (MS) or perinatal nicotine replacement therapy (NRT) impairs hippocampal neurogenesis, neural development and cognitive behaviors in the offspring. Microglia is a source of non-neural regulation of neuronal development and postnatal neurogenesis. In this study, we explored the impact of nicotine on the microglia during the development of hippocampus. Developmental nicotine exposure in a mouse model was conducted by supplementing nicotine in the drinking water to mother mice during gestation and lactation period. We found that juvenile offspring with maternal nicotine exposure presented physical and neurobehavioral development delay, and an increase in anxiety-like behavior in the open field test on post-natal day (PND) 20. To further detect possible developmental neurotoxic effects of nicotine in offspring and underlying mechanism, whole genome microarray analysis of the expression profile of hippocampus was performed on PND 20. Significant alterations in the expression of genes related to inflammatory, neurotransmitter and synapsis were observed in the hippocampus after maternal nicotine exposure, as compared to the vehicle control. Concurrently, an increase in microglial markers and presence of M2 polarity state in the hippocampus of the nicotine offspring were observed by histological analysis and confocal z-stacking scanning. The M2 microglial polarization state was further confirmed with in vitro primary microglia culture by cytokine array, and double positive expression of BDNF/Iba1 in microglia by immunohistochemical staining in the juvenile offspring hippocampus was visualized. We also found that nicotine offspring showed an increase of neurite length in molecular layer and CA1 by Tuj1 staining, as well as an increase in the expression of synapse associated protein, PSD95, but the expression of NeuroD1 in CA1 and CA3 reduced. In summary, maternal nicotine exposure dysregulates immune related genes expression by skewing the polarity of M2 microglia in hippocampus, which may cause abnormal cognitive and behavioral performance in the offspring.